The Effect of Learning Models Children Learning in Science (CLIS) on Student Learning Outcomes in History Subjects Class X11 SMA Negeri 1 Montasik - Fadilla, Hilda; Nurasiah, Nurasiah; Kesuma, T. Bahagia Bahagia (Universitas Syiah Kuala, 2025)
Abstract: This research aims to find out the application of the Children Learning In Science (CLIS) learning model in class XII of SMA Negeri 1 Montasik, and to find out how much influence the Children Learning In Science (CLIS) learning model has on the learning outcomes of class XII students at SMA Negeri 1 Montasik. This research uses a quantitative approach with a type of Pre-experimental design research, in the form of one group pretest posttest design where there is only one group. The population in this study is all students in class XII which is 5 Class. The sample in this study is students in class XII.IPA3 which totals 33 Students. The sampling technique in this study uses Purposive sampling technique. The In data analysis techniques using tests Normality, homogeneity test, and t-test are two average differences. Average value result Before using the Children Learning In Science (CLIS) learning model, which is 60 is categorized as enough and after being given the average student score treatment, which is 80 is categorized as good, this proves that there is a significant change in the student's learning results. Based on the results of the thitung test ttabel or 17,399 2,039 at the significance level of = 5% (0,05), then HO is rejected and Ha is accepted or there is a real (significant) effect on student learning results before and after using the Children Learning In Science (CLIS) learning model in History subjects. Thus, the use of the Children Learning In Science (CLIS) learning model affects the learning results of History students in class XII.IPA3 at SMA Negeri 1 Montasik.